TiO2/CuO films obtained by citrate precursor method for photocatalytic application - Perazolli, Leinig [UNESP]; Nuñez, Luciana [UNESP]; Silva, Milady Renata Apolinário da; Pegler, Guilherme Francisco [UNESP]; Costalonga, Ademir Geraldo Cavallari [UNESP]; Gimenes, Rossano; Kondo, Márcia Matiko; Zaghete, Maria Aparecida [UNESP] (My University, 2011)
In the present work, the hybrid catalyst films of TiO2/CuO containing up to 10% in mol of copper were deposited onto glass surface. Precursor solutions were obtained by citrate precursor method. Films were porous and the average particle size was 20 nm determined by FEG-SEM analysis. The photocatalytic activities of these films were studied using Rhodamine B as a target compound in a fixed bed reactor developed in our laboratory and UV lamp. It was observed that the addition of copper to TiO2 increased significantly its photocatalytic activity during the oxidation of Rhodamine B. The degradation exceeded 90% within 48 hours of irradiation compared to 38% when pure TiO2 was used. Moreover, there was a reduction in the particles band gap energy when compared to that of pure TiO2. These results indicate that the TiO2/CuO films are promising catalysts for the development of fixed bed reactors to be used to treat effluents containing azo dyes.
Keywords: fotocatálise; síntese hidrotérmica; Citrates; Rhodamine B